Cholesterol-lowering Effect of Soy Nuts and Tempeh on Hypercholesterolemic Subjects - Zulaikha, Hermawati Nur; Dijaya Muliadi, Rendy; Kartawidjajaputra, Felicia; Antono, Lina (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2023)
Exploration towards food with cholesterol-lowering property would be beneficial to reduce the incidents of cardiovascular caused by increasing number of people with hypercholesterolaemia. As much as 42 participants with total cholesterol (TC) levels ≥4.92 mmol/L were studied in a three-arms parallel intervention trial. As much as 72g soy nuts and 66g tempeh were consumed daily (25g soy protein/day) for six weeks, while control group was not given any sample. TC level and body composition were measured before and after the treatment for all groups. In soy nuts group, lower TC level was observed (-0.85±0.82 mmol/L, p<0.05) compared to the control group. Meanwhile in tempeh group, non-significant lower TC level was also observed (-0.40±1.19 mmol/L). Differences in body composition parameters were also measured and resulted in significant lower body weight, fat, and visceral fat in soy nuts group (p<0.05) while in tempeh group, only body weight and waist circumference were significantly decreased (p<0.05). This study suggested that daily consumption of soy nuts and tempeh containing 25g soy protein for six weeks showed a tendency to lower TC levels in hypercholesterolaemic-Indonesian participants. A more significant effect might be observed in subject with higher TC levels; and thus, further study is encouraged.